TINGKAT PARTISIPASI ANGGOTA KELOMPOK TANI DALAM KEGIATAN PENANGKARAN BENIH KEDELAI (Glycine max L) DI KECAMATAN RAMAN UTARA KABUPATEN LAMPUNG TIMUR - Dhevi Maryanti; Sumaryo Gs Sumaryo Gs; Suarno Sadar (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aims to analyze the participation level of farmer group members on soybean seed production, and factors related to the participation level. This research was conducted in Rejo Binangun village, North Raman Sub-district. The respondents of this study were 36 soybean farmers selected by using stratified random sampling. The participation level of farmer group members on soybean seed production in this research is analyzed descriptively. The hypothesis was analyzed by using Rank Spearman correlation. The results showed that the participation rate of farmer group members in soybean seed production activities in North Raman sub-district of East Lampung Regency is classified as moderate.  Factors significantly related to the participation rate of members of farmer groups are the type of non-formal education, level of cosmopolitan character, and level of knowledge.Key words:  factors related to participation, participation, soybean seed production